EXAMINATION OF THE RELATIONSHIP BETWEEN FAMILY SELF-CONSTRUALS AND SUICIDAL ATTITUDES - Kazaz, Nalan; Zengin, Dilek Özerhan (International Scientific Journal Vision, 2024)
In our research, the relationship between self-construals and suicide attempts is included. Here, the concept of family is taken into consideration in general. Also; Its definition, elements, features and development are subjected to analysis. Another concept that sheds light on the subject is the self-concept. Once defined self-concept, self-structures are defined, and is divided into two types of self structures is mentioned briefly on the work carried out in Turkey. Then, the concept of suicide is discussed conceptually in a narrow and broad way, the factors underlying suicide are classified, and suicide cases are revealed through numerical data, and a comprehensive literature review is made on the subject. In the same section; The positive and negative reflections of family self-construals and suicidal attitudes on each other, the relationship between them, Turkish and foreign studies on the subject are emphasized.